Construction of the satisfaction scale with synchronous virtual education-ESEVI in students from 12 to 17 years old, Juliaca, 2022 - Carrión Patatingo, Sonia (2022)
To build the Satisfaction Scale with ESEVI synchronous virtual classes capable of measuringthe level of satisfaction in students. Methodology: Non-experimental instrumental design, applied toadolescents between the ages of 12 and 17 who develop synchronous virtual classes. Results: TheESEVI Scale has a content validity index of 97 and a reliability index of .944 by Cronbach’s Alpha and.945 by McDonald’s Omega, likewise, it was processed by exploratory factor analysis ( AFE), it is thusthat 3 dimensions were achieved (virtual classroom, student expectations and pedagogical and familyaccompaniment). Conclusion: The developed instrument meets optimal levels in the required indices.